Artificial Photosynthesis: Visible Light-Activated TiOCl2/2-Phenyl Indole Complexes for Atmospheric CO2 and H2O Capture and Long-Chain Organic Products Generation - Paraskevas, Michail; G. Arzoumanidis, Gregory (Fine Chemical Engineering, 2024)
We present a novel self-organized chemical "living" system that mimics natural photosynthesis by capturing CO2 and H2O from the atmosphere at ambient conditions. This system autonomously reduces CO2 with H2O protons to produce long-chain aliphatic oxygenated products. Starting with 2-phenyl indole (PI) complexes with TiCl4, the hydrolyzed complexes react with CO2 to form organotitanium carbonates. The 2:1 PI/TiCl4 complex was found to be the most effective. Key findings include: Photocatalytic Reduction: Visible light reduces TiIV to TiIII and TiII, forming peroxotitanium complexes and releasing OH radicals. CO2 Reduction: CO2 is reduced to CO, H2CO, and CH3OH, which couple to form HOCH2CH2OH. Organic Compound Synthesis: The system generates oxygenated organic compounds with carbon chains from C2 to C16. Ligand Exchange: The PI ligand exchanges with donor molecules, forming adducts involved in the photocatalytic process. PI Oligomerization: Contributes to the formation of PI oligomers. These processes were monitored using matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) spectra, proton and Carbon-13 nuclear magnetic resonance (13C NMR), and infrared (IR) spectra, identifying over two dozen intermediates and products. This system offers a prototype for new applications with potential improvements using other metals and ligands.